2021
DOI: 10.1111/1462-2920.15688
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns in root and soil fungal diversity drive plant productivity of the desert truffle Terfezia claveryi in plantation

Abstract: The desert truffle Terfezia claveryi is one of the few mycorrhizal fungi currently in cultivation in semiarid and arid areas. Agroclimatic parameters seem to affect its annual yield, but there is no information on the influence of biotic factors. In this study, fungal diversity was analysed by high-throughput sequencing of the ITS2 rDNA region from soil and root samples to compare productive and non-productive mycorrhizal plants in a 4-years old plantation (Murcia, Spain). The fungal metaprofile was dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…This is distinct to the findings of Francisco et al, whereby Chaetomium was not among the top 10 genera identified in plantation soil. This difference may be due to the distinct survival strategies of different types of mycorrhizal edible fungi [ 19 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is distinct to the findings of Francisco et al, whereby Chaetomium was not among the top 10 genera identified in plantation soil. This difference may be due to the distinct survival strategies of different types of mycorrhizal edible fungi [ 19 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Miguel et al [ 16 ] suggested that some fungi, such as species of Boletus , Scleroderma , Pisolithus , and Trichophaea woolhopeia , which often occur in truffle shiros, are closely related to the high yield of target truffles, while other fungi, such as the Hebeloma , Laccaria , and Russula species, are likely to reduce the production of target fruiting bodies. Furthermore, Francisco et al [ 19 ] determined the yield of desert truffle Terfezia claveryi to be affected by the composition of soil and root fungus species, with the production in mycorrhizal roots positively correlated with ectomycorrhizal and arbuscular mycorrhizal fungi, and a positive correlation observed between fungi parasites and plant pathogens in non-producing roots [ 19 ]. To improve the yield and quality of mycorrhizal edible fungi with a high commercial value, researchers have analyzed the soil microbial community characteristics of mycorrhizal edible fungi, such as Tricholoma matsutak , and truffles to improve cultivation techniques and increase yield [ 8 , 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, after 15 a of restoration, the reduction in soil NO 3 --N might hinder the growth of eutrophic microbes. In addition, the decline in SM stimulated the growth of some drought-tolerant bacteria, such as Actinobacteria and Acidobacteria, which were considered as the dominant phyla in harsh and stressful environments (Barka et al, 2016;Arenas et al, 2021). For fungi, SOC content was closely related to the community compositions.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, some abiotic factors or agroclimatic parameters associated with plant management and the control of fungal fruiting have been studied [ 14 , 15 , 16 ]. Although this knowledge on mycorrhizal plant phenology could helped to stabilise annual fluctuations in yield ascocarps production [ 17 ], there are still high fluctuations within the same plantation, resulting in productive and non-productive areas or “patches” [ 18 ]. The analysis of ecology, phenology, and interannual fluctuations on mycelial development are also essential for the proper management of mycorrhizal plants producing truffles or mushrooms [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%